1976
DOI: 10.3109/00365517609081945
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Vitamin A: Serum Concentrations of Zinc and Retinol-Binding Protein (RBP) in Healthy Adolescents

Abstract: The concentrations of serum zinc and retinol-binding protein (RBP) have been studied with special reference to pubertal development in 132 healthy adolescents and young adults (11-26 years of age). The RBP level remained low during the first three of the five stages of puberty (mean, about 30 mg/l). When puberty degree 4 had been reached, the mean RBP level increased to nearly adult values (about 40 mg/l), the boys having somewhat higher levels than the girls. Use of oral contraceptives significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 16 publications
2
15
1
1
Order By: Relevance
“…Although one study of healthy 11-to 26-y-olds reported lowest serum Zn concentrations in boys aged 13-14 y during their first stage of puberty (Michaëlsson et al, 1976), similar findings were not observed in the present study. The lack of significant associations between plasma Zn concentration and any socio-demographic, lifestyle or dietary factor, including Zn intake, in the present study may be due to so few participants having low plasma concentrations.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Although one study of healthy 11-to 26-y-olds reported lowest serum Zn concentrations in boys aged 13-14 y during their first stage of puberty (Michaëlsson et al, 1976), similar findings were not observed in the present study. The lack of significant associations between plasma Zn concentration and any socio-demographic, lifestyle or dietary factor, including Zn intake, in the present study may be due to so few participants having low plasma concentrations.…”
Section: Discussioncontrasting
confidence: 50%
“…A positive correlation between plasma Zn and RBP concentrations was reported in one study (Michaëlsson et al, 1976), although not in another using serum (Lockitch et al, 1988). Although plasma RBP concentration was not measured in the present study, its increase or adequacy in relation to Zn status does provide a plausible explanation for an association between plasma Zn and retinol concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…The authors of a recent study of serum retinol and iron status among adolescent school girls in urban Bangladesh (Ahmed et al, 1996) noted that they were unaware of any other similar information. Studies from developed countries have focused on the pattern of various nutritional parameters during adolescence and the need for age-speci®c reference values (Michae Èlsson et al, 1976;Widhalm et al, 1985;Garry et al, 1987;Lockitch et al, 1988). Some of these studies have demonstrated that levels of plasma retinol or its transport protein are higher during adolescence (Vahlquist et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Devido a isso, os autores sugeriram que rapazes apresentam demanda de zinco aumentada nos primeiros estágios da puberdade. Mesmo classificando os adolescentes nos estadios de Tanner, os que estavam no estirão pubertário foram misturados com os impúberes e os pós-puberdade 25 . Tabela 5 -Concentração de ferro, ferritina, cobre e zinco séricos (µg/dl) nos adolescentes dos sexos masculino e feminino no estirão pubertário Em relação à ferritina, três rapazes e uma moça estavam com valores abaixo do adotado como referência, possivelmente devido à maior formação de massa muscular nos rapazes do que nas moças no período do estirão.…”
Section: Discussionunclassified